Global Standards in the Kampung: Sustainability Standards and their Implications on Indonesian Legal Practice (Standar Global di Kampung: Sustainability Standards dan Implikasinya Terhadap Penerapan Hukum di Indonesia) - Steni, Bernadinus (The Indonesian Journal of Socio-Legal Studies, 2022)
Global market standards have become one of the main instruments to bring all parties towards sustainable resource management. In various sectors, standards for production, including agricultural products, appear in the form of certification labels. One of the most discussed standards today is the sustainability standard. Different from other existing standards, the sustainability standard includes items such as human rights, land rights, and deforestation, which conventionally are the domain of public institutions, especially the government. The global market standards are no longer considered as the work of private sectors, instead it is now the result of traditional institution’s roles transformation and legal implementation processes in various arenas. Therefore, these standards will affect the law-making process and law enforcement. However, the idea of global market standard is repudiated by many people as it is considered a way to eliminate state-sovereignty. To elaborate the extent of the standards’ effect, how they are implemented and interplay with the legal systems, this article studies the implementation of the Roundtable on Sustainable Palm Oil (RSPO) standard in the Palm Oil Plantation in two villages in Central Kalimantan. The situation in the villages portrays the extent of the global market standard implementation. The author hopes this article provides new insight on the relation between global market standards, state law and other norms living, especially, among parties involved in the palm oil industry and farmers’ empowerment. Furthermore, this article is hoped to serve as constructive lesson of a law-making process built on cross-border cooperation.